The Comparative Study of Executive Function between Children with ADHD and Healthy Children - จุลเกตุ, สุดาวรรณ; วิเศษสาธร, มานิกา; พัชโรรส, นนทิมา (Journal of the Psychiatric Association of Thailand, 2019)
Objectives : To study and compare the executive function between children with attention-deficit/ hyperactivity disorder (ADHD) and healthy children Methods : The sample group is 20 children who were newly diagnosed as ADHD according to DSM-5 diagnostic criteria by child and adolescent psychiatrists at psychiatric outpatient unit Ramathibodi Hospital and 20 healthy children with sex, age and education level close to children with ADHD. Executive functions were assessed by Delis-Kaplan executive function system (D-KEFS) nonverbal which is composed of Trail making test, Tower test and Design fluency test. Descriptive statistic were used to calculate frequency, percentage, mean and standard deviation. Dependent t-test and Wilcoxon signed ranks test statistics were used to compare executive function between children with ADHD and healthy children. Results : Children with ADHD have lower executive function than healthy children in the following areas: 1) Self-inhibition average score which was tested by Tower test from the Rule-Violation- Per-Item Ratio (ADHD = 4.40 normal children = 10.60, p <.001) and Total Rule Violations (ADHD = 17.75 normal children = 80.30, p <.001) 2) Cognitive Flexibility average score which was tested by Design fluency test from the total set-loss designs element: score (ADHD = 8.05 Normal children = 11.35, p = .006), total repeated designs: scaled score (ADHD = 11.25 normal children = 12.60, p = .006) and percent design accuracy score (ADHD = 5.60 normal children = 10.80, p <.001) and 3) Planning which was tested by tower test from the total achievement score (ADHD = 8.90 normal children = 11.20, p = .008). While there is no difference in statistical significant in both groups from the Trail making test. Conclusion : Children with ADHD have lower executive function than healthy children in self-inhibition, cognitive flexibility and planning by Tower test and Design fluency test. These tools can differentiate ADHD children from normal children. So they are useful to use as assessment tools to develop executive function rehabilitation programs for children with ADHD which will help and prevent these children together with clinical care and reduce the impact in the long term.